Screening of Brassica juncea Germplasm for Drought Tolerance through Seed Germination and Seedling Growth by using PEG 6000 - DEEPTI SHARMA; NEELAM SETIA; S.S. BANGA (Seed Research, 2026)
One hundred and fifty genotypes of Brassica juncea Czern & Coss were evaluated for their resistance or susceptibility to drought stress on the basis of seed germination and seedling growth. The seeds of all the genotypes were germinated in Petri dishes under drought stress by PEG-6000 (-0.4 and -0.6 MPa). The data recorded on various parameters included germination percentage, shoot and root length, fresh and dry weight of ten-day-old seedlings besides seed testa colour and 100-seed weight of each genotype. Great variations among different genotypes were recorded for these parameters under control conditions, i.e. without PEG treatments. The PEG resulted in reduction of germination potential and seedling growth to varying extent in tested genotypes. On the basis of inhibitory responses for seed germination and seedling growth, due to PEG treatments, the 150 genotypes of B. juncea were categorized as susceptible, moderately resistant and resistant genotypes. Among the resistant genotypes, MLM-90, MLM-91, MLM-44 and MLM-32 indicated their capability to withstand water deficit conditions than other genotypes.